Interfacial formation of intermetallic Ni-Al-Ti systems formed by induction heating - Riyadi, Tri Widodo Besar; Siswanto, Waluyo Adi; Zhu, Xiaomeng (Frontiers in Mechanical Engineering, 2022)
Intermetallic systems of Nickel (Ni), Aluminium (Al), and Titanium (Ti) are candidates for lightweight materials that offer high-temperature resistance. Combustion synthesis has been widely studied to produce intermetallic and coating deposition by exploiting the heat released by the combustion. An underlayer is often used to enhance the adhesion of the coating to the substrate. The interaction of the coating and the underlayer during heating is, therefore, crucial for achieving a good adhesion quality. This work aimed to investigate the microstructure and properties of the interfacial formation across the NiAl coatings and Ti underlayers formed by combustion synthesis. Induction heating was used to initiate the heating and reaction process with heating rates of 46.6, 57.0, and 85.5 K/s. The microstructure was characterized by Scanning Electron Microscopy (SEM) equipped with an Energy Dispersive Spectroscopy (EDS) detector, whereas the formed phases were identified using X-ray Diffraction (XRD) tests. The hardness distribution was measured by the Vickers microhardness test. The result shows that NiAl with Al-rich and Ni-rich were formed in the coating region. The average thickness of the coating increases by approximately 200, 300, and 400 µm with a heating rate of 46.6, 57.0, and 85.5 K/s, respectively. The different thicknesses of the coating can be attributed to the migration of Ni/Al from the coating to the underlayer zones. The microstructure observed in the underlayer confirms the formation of several intermetallic phases of Ni-Ti and Ti-Al systems. The infiltration of Ni and Al elements from Ni and Al to Ti sides was responsible for generating a reaction between Ni-Ai-Ti. The formation of Ti2Ni–Ti3Al phases in the underlayer increases with the heating rate. The hardness across the coating, interface, and underlayer increases with the heating rates. The heating rate of 46.6, 57.0, and 85.5 K/s results in the hardness of the interface by 669.1, 804.8, and 967.7 HV, whereas the underlayer increases by 680.1, 772.7, and 978.7 HV, respectively. The increased content of the Ni-Al-Ti system, which are AlNi2Ti and Ti2Ni–Ti3Al phases, was attributed to the increased hardness of the interface and underlayer. This work improves the understanding of second reactions across the interface while fabricating coatings that apply an underlayer.